factor 2x(x^2 -x -6)

(2) Answers

if you want to factor this question you should only factor x^-x-6 so you will have: x^2 -x -6 = (x-3)(x+2)  so now you have: 2x(x-3)(x+2) and that is the answer :)))) i hope this is helpful have a nice day 


ok so you can leave the 2x out since that is already a factor form is normally ax^2+bx+c a=first term b=second term c=third term so now we look at the first terms it is 1 good now we look at the value of the middle and lastt term second term=-1 third term=-6 we need to find what 2 factors of -6 add to -1 -6=-3 times 2 -3+2=-1 (x-3)(x+2) so the factored form is (2x)(x-3)(x+2)

Add answer